Hadith #508 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Sulaiman bin Musa al-Ashdaq سليمان بن موسى الأموي الأشدق; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to pray ‘Asr, then a person could go to Quba’.” One of them said: “And he would come to them when they were prayed.” The other said: “And the sub was still high.” Both Az-Zuhri and Ishaq bin ‘Abdullah narrated it from Anas, so the reference is about them.
Grade:

Hadith #1201 - Sunan al-Nasa'i - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; al-Husain bin Hryth الحسين بن حريث; ibn Abbas; Ikrama عكرمة; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“Aishah said: ‘Turning around during prayer is something that the Shaitan snatches from one’s prayer.'”
Grade:

Hadith #2165 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Khalid bin Ma'dan خالد بن معدان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“Masruq and I came to ‘Aishah, and Masruq said to her: ‘There are two men from among the Companions of the Messenger of Allah both of whom are good; one of them delays the prayer and Ifar, and the other hastens the prayer and Iftar.’ ‘Aishah said: ‘Which of them is the one who hastens the prayer and Iftar?’ Masruq said: ‘That is what the Messenger of Allah used to do.”‘
Grade:

Hadith #2187 - Sunan al-Nasa'i - Abdullah bin Da'ud al-Kharaybi عبد الله بن داود أبو عبد الرحمن الخريبي; Aisha bint Abi Bakr; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Khalid bin Ma'dan خالد بن معدان; Rabi'yah al-Jrshy ربيعة الجرشي; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“I do not know that the Messenger of Allah recited the whole Quran in one night, or prayed Qiyam until morning, or ever fasted an entire month except Ramadan.” ‘
Grade:

Hadith #2361 - Sunan al-Nasa'i - Abdullah bin Da'ud al-Kharaybi عبد الله بن داود أبو عبد الرحمن الخريبي; Aisha bint Abi Bakr; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Khalid bin Ma'dan خالد بن معدان; Rabi'yah al-Jrshy ربيعة الجرشي; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“The Messenger of Allah used to fast all of Shaban.”
Grade:

Hadith #2362 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Khalid bin Ma'dan خالد بن معدان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“I said: ‘O Messenger of Allah, I do not see you fasting any month as much as Shaban.’ He said: ‘That is a month to which people do not pay much attention, between Rajab and Ramadan. It is a month in which the deeds are taken up to the Lord of the worlds, and I like that my deeds be taken up when I am fasting.”‘
Grade:

Hadith #2577 - Sunan al-Nasa'i - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Amr bin Mnswr al-Nsa'iy عمرو بن منصور النسائي أبو سعيد; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“The poor man (Miskin) is not the one who goes around asking people and they send him away with a morsel or two, of a date or two. “They said: “Then what does poor (Mishkin) mean?” He said: “The one who does not possess independence of means and no one notices him to give charity to him, and he does not stand and ask of people.”
Grade:

Hadith #3671 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; al-Rabi' bin Sulaiman الربيع بن سليمان; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
Sa’d bin ‘Ubadah came to the Prophet and said: “My mother has died and she had a vow to fulfill but she did not do so.” He said: “Fulfill it on her behalf.”
Grade:

Hadith #3827 - Sunan al-Nasa'i - Abu Hurairah; al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
“Sa’d bin ‘Ubadah asked the Messenger of Allah about a vow which his mother had sworn, but she died before she could fulfill it. The Messenger of Allah said: ‘Fulfill it on her behalf.'”
Grade:

Hadith #3984 - Sunan al-Nasa'i - Abu Idrees al-Khulani أبو إدريس الخولاني; Muhammad bin 'Ubaidullah bin Sa'id محمد بن عبيد الله بن سعيد أبو عون الثقفي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Safwan bin 'Isa al-Zhry صفوان بن عيسى الزهري أبو محمد البصري; Thur bin Zayd al-Dayli ثور بن زيد (Sunan al-Nasa'i)
The Messenger of Allah said: “I have been commanded to fight the people until they say La ilaha illallah, and whoever says it, his life and his wealth are safe from me, except for a right that is due, and his reckoning will be with Allah.”
Grade:

Hadith #2710 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
A man from the Companions of the Prophet (ﷺ) died on the day of Khaybar. They mentioned the matter to the Messenger of Allah. He said: Offer prayer over your companion. When the faces of the people looked perplexed, he said: Your companion misappropriated booty in the path of Allah. We searched his belongings and found some Jewish beads not worth two dirhams.
Grade: Hasan

Hadith #2719 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Auf bin Malik al-Ashja'i; Jubayr bin Nufayr al-Hadrami; Khalid bin Ma'dan خالد بن معدان; Nufayr bin Malik al-Hadrami; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
‘Awf bin malik Al Ashja’I said “I went out with Zaid bin Harith in the battle of Mutah. For the reinforcement of the Muslim army a man from the people of Yemen accompanied me. He had only his sword with him. A man from the Muslims slaughtered a Camel. The man for the reinforcement asked him for a part of its skin which he gave him. He made it like the shape of a shield. We went on and met the Byzantine armies. There was a man among them on a reddish horse with a golden saddle and golden we
Grade: Sahih

Hadith #2802 - Sunan Abi Dawud - Abu Hameed al-R'yny أبو حميد الرعيني; Ali bin Bhr bin Bry علي بن بحر بن بري; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
I asked al-Bara’ ibn Azib: What should be avoided in sacrificial animals? He said: The Messenger of Allah (ﷺ) stood among us, and my fingers are smaller than his fingers, and my fingertips are smaller than his fingertips. He said (pointing with his fingers): Four (types of animals) should be avoided in sacrifice: A One-eyed animal which has obviously lost the sight of one eye, a sick animal which is obviously sick, a lame animal which obviously limps and an animal with a broken leg with no m
Grade: Sahih

Hadith #2873 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
I memorised (a tradition) from the Messenger of Allah (ﷺ): There is no orphanhood after puberty, and there is no silence for the whole day till the night.
Grade: Sahih

Hadith #3848 - Sunan Abi Dawud - Abu Umama bin Sahl; Khalid bin Ma'dan خالد بن معدان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Thur bin Zayd al-Dayli ثور بن زيد; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) used to eat with three fingers and not wipe his before licking it.
Grade: Sahih

Hadith #4179 - Sunan Abi Dawud - Abdul 'Aziz bin 'Abdullah al-Uvaisi عبد العزيز بن عبد الله بن يحيى الأويسي; al-Hasan al-Basri الحسن البصري; Ammar ibn Yasir; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade men to use saffron. Isma’il version has: “(forbade) man to use saffron.”
Grade: Sahih

Hadith #4886 - Sunan Abi Dawud - Isa bin Muhammad bin al-Nahas عيسى بن محمد بن النحاس; Mu'awiya ibn Abu Sufyan; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي; Rashid bin Sa'd راشد بن سعد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
Is one of you helpless to be like AbuDaygham or Damdam (Ibn Ubayd is doubtful) who would say when morning came: O Allah, I gave my honour as alms to Thy servants?
Grade: Da'if

Hadith #5052 - Sunan Abi Dawud - Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Khalid bin Ma'dan خالد بن معدان; Thur bin Zayd al-Dayli ثور بن زيد; Yahya bin Hamza bin Waqd يحيى بن حمزة بن واقد; Yahya bin Hsan يحيى بن حسان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to say when he lay down: O Allah, I seek refuge in Thy noble Person and in Thy perfect Words from the evil of what Thou seizest by its forelock; O Allah! Thou removest debt and sin; O Allah! thy troop’s not routed, Thy promise is not broken and the riches of the rich do not avail against Thee. Glory and praise be unto Thee!.
Grade: Da'if

Hadith #5122 - Sunan Abi Dawud - Habib bin 'Ubaid al-Rhby حبيب بن عبيد الرحبي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Thur bin Zayd al-Dayli ثور بن زيد; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
the son of a sister of a people belongs to them.
Grade: Sahih

Hadith #587 - Jami' al-Tirmidhi - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; ibn Abbas; Ikrama عكرمة; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Thur bin Zayd al-Dayli ثور بن زيد (Jami' al-Tirmidhi)
“The Messenger of Allah would glance toward the right and the left during Salat but he would not turn his neck to look behind him.”
Grade:

Hadith #2031 - Jami' al-Tirmidhi - Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ma'n bin 'Isa bin Yahya معن بن عيسى بن يحيى; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد (Jami' al-Tirmidhi)
“Charity does not diminish wealth, Allah does not increase a man in anything for his pardoning (others) but in honor, and none humbles himself for Allah but Allah raises him.”
Grade:

Hadith #3540 - Jami' al-Tirmidhi - Abdullah ibn Ja'far; Abu Hurairah; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد (Jami' al-Tirmidhi)
“Allah created a hundred mercies, and He placed one mercy among his creation, they show mercy to one another by it, and there are ninety-nine mercies with Allah.”
Grade:

Hadith #2124 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Ibn Ishaq محمد بن إسحاق بن يسار‎; Safiyya bint Shayba bin 'Uthman; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Ibn Majah)
the Messenger of Allah (ﷺ) said: “Do not take back your charity.”
Grade:

Hadith #2223 - Sunan Ibn Majah - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني (Sunan Ibn Majah)
“The land around a date-palm tree, as far as its branches reach, belongs to the owner of the tree.”
Grade:

Hadith #2502 - Sunan Ibn Majah - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘For guarding the frontier for a day in the cause of Allah, defending the Muslims, seeking reward, apart from in the month of Ramadan, there is a reward granted greater than worshipping for a hundred years, fasting and praying. Guarding the frontier for a day in the cause of Allah, defending the Muslims, seeking reward, in the month of Ramadan, is better before Allah and brings a greater reward” – I think he said – “than worshipping for a thousand
Grade: